Between Lineage Scholarship and Charisma: The Phenomenon of Habib and Gus in Islamic Education - Arifin, Syamsul; Hasnun Umar; Zaenudin Mudaham Amin; Yasril Gunawan; Khoiriyah (Education Reserach Center, 2026)
This study aims to analyze the configuration of religious authority of Habib and Gus in contemporary Islamic education within the digital sphere, examining how nasab, pesantren scholarship, and charisma are constructed, reproduced, and contested on social media. The research employs a qualitative approach with an interpretative case study design. Data were collected through in-depth interviews with Habib, Gus, santri, Islamic Religious Education teachers, and digital congregants; participatory observation of online da'wah activities and documentation study of social media content and digital da'wah archives. Data analysis was conducted using the interactive model of Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña, grounded in the theoretical framework of authority proposed by Max Weber and the theory of symbolic capital developed by Pierre Bourdieu. The findings indicate that the authority of Habib on social media is primarily constructed through nasab as symbolic capital, which gains legitimacy through collective recognition and digital representation. In contrast, the authority of Gus is more dominantly grounded in scholarship and pesantren based sanad, representing the continuity of Islamic intellectual tradition. Furthermore, the study identifies the emergence of digital charisma, formed through communicative performativity, emotional interaction, and technological mediation, thereby reinforcing audience loyalty within virtual communities. Social media functions as a new religious arena that both expands and intensifies symbolic contestation between genealogical legitimacy and scholarly legitimacy.